A poética negativa de João Cabral de Melo Neto - Felipe Oliveira de Paula (2018)
The aim is to investigate the work of João Cabral de Melo Neto if the questioning of the language and besides it reflecting the literary technical elements, promotes a criticism that is directed to social devices, which, in turn, trigger these questions. This criticism is not established only in the subject, or in the poem in which the historical movement presents itself in a more referential way, but in the process of identification and non-identification of given images to express matter. Therefore, we search in Part one how poetry cabralina is config-ured to assimilate and reject poetic tools sedimented in literary tradition, such as the block, an enhanced vision about the reality in the 1930's and aesthetic options present in some contem-poraries: the members of the call "Generation of 45" and concretistas. These discussions make it possible to understand a particularity of cabralina poetry and, at the same time, to discuss aspects pointed out by its critical fortune. In addition, in order to understand the poetic pro-gram of the poet from Pernambuco and to outline what we call negative poetics, we study, in Part two, the book Os três mal-amados and the poem Fábula de Anfion more closely. To aid reflection on negativity, we rely on the concept developed by Theodor Adorno in Negative Dialectics. Already in Part 3, when analyzing some poems, we intend to take advantage of the discussions developed in the previous chapters and to understand the negative poetics of João Cabral.